The Role of Student’s Parents in Education at Public Elementary School 3 of Jatiluhur - Purwanti, Dwi (Universitas Sebelas Maret, 2019)
Educational development in Indonesia needs the participation of parents and the community and the school itself. These three elements must work together in an effort to realize the goals of education in schools. Parents of students were originally only concentrated in supporting the education of children in the family, now it is developing in the involvement of parents in the administration of education in schools, including those that occur in SD Negeri 3 Jatiluhur. This study focuses on: (1) what is the role of parents in education ?; (2) what is the form of parental participation in SD Negeri 3 Jatiluhur? The results of this study include: (1) the participation of parents in education, namely the involvement of parents in organizing their children's education in schools; (2) the form of parental participation in SD Negeri 3 Jatiluhur is to attend meetings held by the school, attend the parent / guardian class, become a member of the school committee, as a companion to extracurricular activities, play an active role in the activities carried out by the school committee, play an active role in the activities of Strengthening Children's Character Education in schools.